Material and Social Assistance to Military Families in Years of Great Patriotic War (on Materials of North Ossetia) - L. C. Khabliyeva; U. S. Tedeyeva (Научный диалог)
The work of the state authorities to assist military families in the years of the Great Patriotic war is considered. The article focuses on financial provision for this category of citizens. The problem of food supply and necessities is examined. The question is raised about the structure of government providing aid to servicemen. Special attention is paid to information on the provision of material assistance. The research urgency is caused by the fact that the historical experience of building the system to assist military families shows that the army is not able to solve the tasks without active social support. Novelty of research consists in the fact that the successes and shortcomings of the social work carried out by the authorities of the North Ossetian ASSR, and attempts to overcome the difficulties for the first time are shown on the basis of archival materials. To a certain extent the gaps are filled in the study of topics such as logistical supply of members of military families, their employment, social interactions and, in particular, nation-wide assistance to this category of population at the regional level. For the first time the materials of Central state archive of the Republic of North Ossetia-Alania on the topic are introduced into scientific circulation. The author comes to the conclusion that in the years of the Great Patriotic war, military families are not left without attention of the state, society, enterprises and organizations. Their activities are comprehensive and complementary.